PERTIMBANGAN HAKIM DALAM PENJATUHAN PUTUSAN LEPAS DARI SEGALA TUNTUTAN HUKUM KEPADA PELAKU TINDAK PIDANA PENGRUSAKAN SECARA BERSAMA-SAMA - Giawa, Kaima (LPPM Universitas Nias Raya, 2025)
Criminal trespass is breaking the law and damaging someone else's property or property. A decision to find a defendant not guilty of all charges is a judicial decision that the defendant's actions did not constitute a crime. Resolution No. 404/Pid.B/2018/PN Pbr is one of the resolutions in which the accused was acquitted of all charges. Therefore, the aim of this study is to know and analyze the reasoning of the judges when deciding whether to drop all legal charges against the authors. This study collected secondary data including primary legal data, secondary legal data and third legal data and used the traditional legal research method which uses legal legal approach, case approach and analytical approach. Based on the observations and discussions, it can be concluded that the judges took into account the decision to jointly formulate all legal charges against the perpetrators of the crime (Decision No. 404/Pid.B /2018/PN Pbr). ) in relation to article 170.1. A witness Hendry Liberty. The couple claimed to own the land where the crime took place, and the accused and witnesses were able to prove this with land ownership certificates from both parties. The authors suggest that law enforcement officials, especially prosecutors, should pay more attention or investigate more deeply the cases they handle to avoid confusing the judge by dismissing all charges against the accused judge.